Hemin controls T cell polarization in sickle cell alloimmunization - Zhong, Hui (2014)
Patients with sickle cell disease (SCD) often require transfusions to treat and prevent worsening anemia and other SCD complications. However, transfusions can trigger alloimmunization against transfused red blood cells (RBCs) with serious clinical sequelae. Risk factors for alloimmunization in SCD remain poorly understood. We recently reported altered regulatory T cell (Treg) and T helper (Th) responses with higher circulating Th1 (IFN-γ+) cytokines in chronically transfused SCD patients with alloantibodies as compared to those without alloantibodies. Since monocytes play a critical role in polarization of T cell subsets and participate in clearance of transfused RBCs, we tested the hypothesis that in response to RBC breakdown product, hemin, monocyte control of T cell polarization will differ between alloimmunized and non-alloimmunized SCD patients. Exogenous hemin induced Treg polarization in purified T-cell-monocyte cocultures from healthy volunteers through monocyte anti-inflammatory heme degrading enzyme HO-1. Importantly, hemin primarily through its effect on CD16+ monocytes induced an anti-inflammatory (higher Treg/lower Th1) polarization state in non-alloimmunized SCD group, whereas it had little effect in the alloimmunized group. Non-alloimmunized SCD CD16+ monocytes expressed higher basal levels of HO-1. Furthermore, IL-12, which contributed to a pro-inflammatory polarization state (low Treg/high Th1) in SCD, was dampened in hemin-treated stimulated monocytes from non-alloimmunized SCD patients, but not in alloimmunized group. These data suggest that unlike alloimmunized patients, non-alloimmunized SCD CD16+ monocytes in response to transfused RBC breakdown products promote an anti-inflammatory state that is less conductive to alloimmunization.